2005
DOI: 10.2214/ajr.185.3.01850622
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Cryptococcosis in Immunocompetent Patients: CT Findings in 12 Patients

Abstract: The CT manifestations of pulmonary cryptococcosis consist of pulmonary nodules or masses measuring 5-52 mm in diameter and focal areas of consolidation. The nodules and masses have a predominantly peripheral distribution in 80% of the cases. Cavitation of nodules or consolidation is seen in approximately 40% of the cases. The infection can be due to Cryptococcus neoformans var gattii or var neoformans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
51
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 27 publications
19
51
3
1
Order By: Relevance
“…Surrounding groundglass opacity or the CT halo sign, as found in our study, and isolated groundglass opacity (6,(8)(9)(10)(11)17) can be observed. Although centrilobular or satellite nodules have been described (6,8), tree-inbud appearance was observed neither in the present nor in previous studies (6)(7)(8)(9). Therefore, we suggest that the presence of nonenhanced low-attenuation areas within the areas of consolidation or mass having peripheral, subpleural and lower lung predominance, as shown in the present study, should raise the concern for pulmonary cryptococcosis, particularly in a patient presenting with meningitis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Surrounding groundglass opacity or the CT halo sign, as found in our study, and isolated groundglass opacity (6,(8)(9)(10)(11)17) can be observed. Although centrilobular or satellite nodules have been described (6,8), tree-inbud appearance was observed neither in the present nor in previous studies (6)(7)(8)(9). Therefore, we suggest that the presence of nonenhanced low-attenuation areas within the areas of consolidation or mass having peripheral, subpleural and lower lung predominance, as shown in the present study, should raise the concern for pulmonary cryptococcosis, particularly in a patient presenting with meningitis.…”
Section: Discussionsupporting
confidence: 81%
“…Calcification within the pulmonary lesion, as shown in one of our cases, is also rare (14,15,17,18). Surrounding groundglass opacity or the CT halo sign, as found in our study, and isolated groundglass opacity (6,(8)(9)(10)(11)17) can be observed. Although centrilobular or satellite nodules have been described (6,8), tree-inbud appearance was observed neither in the present nor in previous studies (6)(7)(8)(9).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The clinical expression is variable and may present as coughing, expectoration, chest tightness, fever or asymptomatic. The most common radiological characteristics are known to be solitary or multiple pulmonary nodules, and segmental or lobar consolidation (10,11). For these reasons, pulmonary cryptococcosis is frequently misdiagnosed as other lung diseases, such as cancer and pneumonia.…”
Section: Plain and Contrast-enhanced Chest Computed Tomography Scan Fmentioning
confidence: 99%